2008
DOI: 10.1002/ceat.200800238
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Ignition in Catalytic Microreactors

Abstract: A pseudo-2D reactor model is used to perform a comprehensive study on the catalytic ignition of a lean propane/air mixture in a microreactor with Pt-coated walls. The results of the in-house code are verified against the commercial package FLUENT. The roles of inlet velocity, wall conductivity, heat losses or heat transfer to an adjacent endothermic channel, channel gap size, and wall thickness in steady-state ignition via inlet preheating and resistive heating, are studied. The results show that the heat loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
6
15
0
Order By: Relevance
“…The equations are written in the axial direction; transverse heat and mass fluxes between the bulk and the wall are accounted for through lumped transport coefficients, which depend on the Nusselt and Sherwood numbers. In previous work Stefanidis et al, 2008), we found that average, constant values of 4 and 3.8 for the Nu and Sh number, respectively, result in good quantitative agreement between our pseudo-2D code (2004). The grid in the axial direction consists of 500 equally spaced nodes.…”
Section: Multifunctional Device Modelsupporting
confidence: 87%
“…The equations are written in the axial direction; transverse heat and mass fluxes between the bulk and the wall are accounted for through lumped transport coefficients, which depend on the Nusselt and Sherwood numbers. In previous work Stefanidis et al, 2008), we found that average, constant values of 4 and 3.8 for the Nu and Sh number, respectively, result in good quantitative agreement between our pseudo-2D code (2004). The grid in the axial direction consists of 500 equally spaced nodes.…”
Section: Multifunctional Device Modelsupporting
confidence: 87%
“…The catalytic ignition of fuel-air mixtures has received considerable attention in the literature in the past few years, due to its role in start-up in automobile catalytic converters and in catalytic and catalytically assisted combustors [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Experimental and theoretical studies of catalytic ignition have been published, increasing our knowledge about several aspects related with this type of critical nonlinear process.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis has been applied to methane-air mixtures on a platinum catalyst [22], where the global reaction rate has been obtained in closed form and is to be employed in this work. Recently, a large amount of work has been published on catalytic ignition and combustion in microreactors [6][7][8][9][10][11][12][13][14], where further references are listed. In most of the theoretical works, a commercial code has been used to study the catalytic combustion in narrow channels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in micro/meso-propulsion related to scaling laws issues [3][4][5][6] and focuses predominantly on fluid dynamics and combustion [7][8][9][10][11][12][13][14][15][16][17][18]. Three dimensional numerical simulations of methane-air combustion in swirling micro/meso-combustors are not common: the majority of the references available in the literature investigate the combustion process of propane in micro/meso sized combustor by assuming 2-D axi-symmetrical geometry and reduced kinetic mechanism [7][8][9][10][11][12][13][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensional numerical simulations of methane-air combustion in swirling micro/meso-combustors are not common: the majority of the references available in the literature investigate the combustion process of propane in micro/meso sized combustor by assuming 2-D axi-symmetrical geometry and reduced kinetic mechanism [7][8][9][10][11][12][13][16][17][18].…”
Section: Introductionmentioning
confidence: 99%